2021
DOI: 10.1039/d1ra04046d
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effects between boron and nitrogen atoms in BN-codoped C59−nBNnfullerenes (n= 1–3) for metal-free reduction of greenhouse N2O gas

Abstract: The synergic effects between B and N atoms make C57BN2 and C56BN3 highly active catalysts for reduction of greenhouse N2O gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…It is worth noting that when the carbon atoms are replaced by elements such as N and B, for example, the character of the MESP surface changes in such a way that the surfaces of N and B progressively become more electrophilic. This specific feature has been discussed by Esrafili and coworkers 90 for C 59 B, C 58 BN, C 57 BN 2 and C 56 BN 3 , in which the uniformity of charge density distribution observed on the electrostatic surface of the C 60 is distorted by the substitutions. The N-doped C 60 fullerene was shown to be a potential cathode catalyst for hydrogen fuel cells.…”
Section: Resultsmentioning
confidence: 59%
“…It is worth noting that when the carbon atoms are replaced by elements such as N and B, for example, the character of the MESP surface changes in such a way that the surfaces of N and B progressively become more electrophilic. This specific feature has been discussed by Esrafili and coworkers 90 for C 59 B, C 58 BN, C 57 BN 2 and C 56 BN 3 , in which the uniformity of charge density distribution observed on the electrostatic surface of the C 60 is distorted by the substitutions. The N-doped C 60 fullerene was shown to be a potential cathode catalyst for hydrogen fuel cells.…”
Section: Resultsmentioning
confidence: 59%
“…The approach of employing B,N-doped and co-doped fullerenes as catalysts for LABs is a logical choice, as both nitrogen and boron atoms can synergistically activate the inert carbon π electrons. 33 As the ORR/OER performance of catalysts in LABs is significantly affected by the existence of lithium atoms, it is important to clarify whether N and B co-doped fullerenes still show a synergetic effect in LABs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that the curvature and pentagon defects inherent in fullerenes make them promising candidates as electrocatalysts for the ORR. [32][33][34] Kim et al 35 synthesized a graphene chip as the cathode in an ether-based electrolyte and reported a high coulombic efficiency of 99% for the first cycle in LABs. Furthermore, heteroatom-doped carbon materials have been extensively studied for ORR and OER.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations